Perlindungan Hak Asasi Manusia bagi Kelompok Agama Minoritas dalam Pendirian Tempat Ibadah - Nadia Gloria Sanger; Wenly R. J. Lolong; Merry Lenda Kumajas (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research discusses the protection of human rights (HAM) for religious minorities in Indonesia in the context of the establishment of places of worship. Indonesia, as a country with diverse ethnicities, cultures, and religions, guarantees freedom of religion through the 1945 Constitution and Pancasila. However, religious minority groups often face various challenges and discrimination in establishing places of worship, which has the potential to cause interfaith conflict and threaten the disintegration of the nation. This research uses normative legal research method or literature study to analyze related laws and regulations, especially the Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs Number 8 and 9 of 2006 (PBM No. 8 & 9/2006) which regulates the establishment of houses of worship. Problems that often arise include licensing difficulties such as Building Construction Permit (IMB), rejection from the majority community, administrative manipulation, to acts of intolerance in the form of prohibition, forced closure, and even destruction of places of worship. This study aims to identify problems in law enforcement related to the human rights of minority groups in establishing places of worship and analyze the effectiveness and impact of existing regulations, such as PBM No. 8 & 9/2006, on efforts to fulfill these rights and maintain religious harmony in Indonesia.